Acceptance Analysis of Accounting Software User though Technology Acceptance Model - Irawan Irawan (Politeknik Negeri Lampung, 2015)
This research conducted to find out the quality of the Islamic financial accounting information of BMT in the city of Bandar Lampung. The object of research is the quality of financial accounting information consisting of relevance , reliability, comparability, consistency, and understandability by distributing questionnaires to 13 BMTs which are active in the city of Bandar Lampung. The research indicates that the quality of Islamic financial accounting information of BMTs in the city of Bandar Lampung is good.Key words: accounting information, the quality, BMT